PELAKSANAAN PERJANJIAN KERJA ANTARA SUPIR DAN PENGUSAHA JASA ANGKUTAN PADA CV. ALEXSANDER TRAVEL - Marpaung, Enra Alexsander; Deliana, Evi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Civil Code, Article 1313 of the formulation of the Contract or the Agreement, Article 1338 all agreements made by fulfilling the conditions prescribed by the Act are the Laws for those Who Make It. Law Number 13 Year 2003 concerning Manpower, Article 51 Paragraph 1 agreement made in writing. CV. Alexsander Travel has business in public transportation services, route Pekanbaru-Jambi PP. Its work system is contained in a work agreement that has been blessed. The purpose of writing this thesis, namely to know the implementation of existing work agreements on CV.Alexsander with driver. This type of research is classified in the type of research of Sociological Law, namely research on the effectiveness of the current law, the nature of this research is descriptive research that describes systematically, facts and characteristics of the object studied appropriately. Research conducted at CV.Alexsander travel intersection arengka 2 ring road Pekanbaru, while the population and sample are all parties related to this research, whether it is businessmen, and workers / drivers. Sources of data used are primary data and secondary data, data collection techniques used are interviews and questionnaires. From the results of research problems there are three main things that can be concluded that First, the implementation of the work agreement on CV.Alexsander travel has not been fulfilled in its entirety. Second, the obstacles in implementing the work agreement there are internal factors, related to the performance of the driver is less than the maximum, as well as external factors related to the proliferation of travel-dark travel that does not have route permission. Third Efforts that can be done by each Party is to work maximally, to make achievements according to the contents of the employment agreement, as well as support of the Department of Transportation related to conducting raid operations on illegal transport and transportation that does not have route permission. Suggestion of the writer, the parties who carry out the contents of the work agreement, do seriously or with legal awareness, make achievements on the contents of the employment agreement, so that all try to maximize, to minimize the barriers all parties must synergize in advancing the company, the effort that can be done is by exercising their respective obligations in order to gain their respective rights as well. Keywords: Implementation of work agreement, CV.Alexsander travel, driver